Information System for Predicting Warehouse Stock and Utilities (Case Study: PT KERAMIK XYZ) - Yushintia Pramitarini; Pramana Yoga Saputra; Alindya Kirana Putri (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2021)
PT KERAMIK XYZ is one of the companies engaged in the production of ceramics. The company sometimes subjected to declining wall tiles on the market and at warehouses where wall ceramic stocks are sometimes subjected to buildup. Therefore, the research of